2013
DOI: 10.1016/j.neuroscience.2013.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory solitary tract development: A role for neuropilins

Abstract: The rostral nucleus of the solitary tract (rNST) receives orosensory information from taste bud cells in the tongue and palate via cranial nerves VII and IX. These nerves enter the brainstem, form the solitary tract (ST) and synapse with neurons in the rNST, which then relay incoming sensory information to other brain areas to process external gustatory stimuli. Factors that direct or regulate the trajectory of the developing ST are largely unknown. We used DiI to identify ST projections originating from cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Importantly, the brainstem’s pons and medulla have the highest expression of ACE2 . More recently, neuropilin-1 has been confirmed as a co-receptor that facilitates SARS-CoV-2 infection into cells, especially in the olfactory epithelium where ACE2 expression is relatively low. , Interestingly, neuropilin-1 is also expressed in the brainstem of developing animal brains. , Thus, the mature brainstem may also express neuropilin-1 that promotes SARS-CoV-2 infection.…”
Section: Sars-cov-2 Tropism For the Brainstemmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the brainstem’s pons and medulla have the highest expression of ACE2 . More recently, neuropilin-1 has been confirmed as a co-receptor that facilitates SARS-CoV-2 infection into cells, especially in the olfactory epithelium where ACE2 expression is relatively low. , Interestingly, neuropilin-1 is also expressed in the brainstem of developing animal brains. , Thus, the mature brainstem may also express neuropilin-1 that promotes SARS-CoV-2 infection.…”
Section: Sars-cov-2 Tropism For the Brainstemmentioning
confidence: 99%
“… 51 , 52 Interestingly, neuropilin-1 is also expressed in the brainstem of developing animal brains. 53 , 54 Thus, the mature brainstem may also express neuropilin-1 that promotes SARS-CoV-2 infection.…”
Section: Sars-cov-2 Tropism For the Brainstemmentioning
confidence: 99%
“…The role of the neuropilin (Npn) receptors and their semaphorin (Sema) ligands in axonal growth is well known in various sensory and motor neural systems (Neufeld et al, 2002;Meléndez-Herrera and Varela-Echavarría, 2006;Pasterkamp, 2012). In the hindbrain, Nrp1 and Sema3A were found to form gradients across the projections of A1-derived pontine axons (Solowska et al, 2002), whereas Npn-1/2 were shown to be expressed in axons projecting from the NTS, which contain dA3-derived neurons (Corson et al, 2013). These spatiotemporal expression patterns indicate that the Npn and Sema families of axon guidance molecules are potential molecular regulators for dA1 and dA3 axonal trajectories.…”
Section: Neuropilin/semaphorinmentioning
confidence: 99%
“…The XII nerve guides the muscle activity of most of the contractile districts, while the X nerve, in addition to giving parasympathetic fibers, is activated by the contraction of the palatoglossus muscle (an extrinsic muscle of the tongue) [ 7 , 8 ]. The lingual nerve innervates the anterior portion for gustatory and somatic sensitivity and anastomoses with afferent fibers of the cranial facial nerve or VII (cord of the eardrum) [ 9 ]. Sympathetic fibers arrive at the lingual musculature from the superior cervical ganglion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%